A Twisted Block Tangential Filtering Decomposition Preconditioner. (23rd March 2009) - Wang, Ruirui; Niu, Qiang; Lu, Linzhang
Abstract : For block-tridiagonal linear system of equations, a variant of tangential filtering preconditioners is proposed in this paper. The new variant is based on a twisted block factorization along with certain filtering property. For practical usage, a class of composite preconditioners tested, which are constructed by combining the twisted tangential filtering decomposition preconditioner with the classicalI L U ( 0 ) preconditioner in a multiplicative way. The performance of the new preconditioners is compared with other classical preconditioners; the superiority and the weakness of the preconditioners are pointed out.